The water extract of "Jiao Mei Gu" attenuates the lipopolysaccharide-induced inflammatory response via inhibiting NF-κB activity in mice. (15th September 2020) - Luo, Li; Zhang, Wei; Zhang, Zaiqi; Zhu, Junyu; Li, Wei; Yi, Yuhao; Yang, Xue; Ma, Wei; Liang, Huaping
Abstract: Ethnopharmacological relevance: Jiao Mei Gu (JMG), Cayratia albifolia C.L.Li, is a type of Dong plant widely growing in Dong autonomous counties, Hunan province, China. As a type of traditional herbal medicine, the root of JMG plant has been used to treat inflammatory-related diseases such as arthritis because of its prominent anti-inflammatory effects in Dong medicine. Aim of the study: This work investigated the anti-inflammatory effects and mechanisms of the water extract from the root of JMG on lipopolysaccharide (LPS)-induced inflammatory models. Methods: Endotoxemia was induced in C57BL/6 mice by intraperitoneal injection of LPS (20 mg/kg), meanwhile intraperitoneal administration of safe doses of JMG. The survival curve of mice was determined. Serum inflammatory cytokines were detected by the Bio-Plex Mouse Cytokine 23-Plex Panel Kit and enzyme-linked immunosorbent assay (ELISA) at 6 h after drug treatment. Hematoxylin-eosin (HE) staining of important organs was completed at 24 h after treatment. The mechanism of inflammatory action was investigated in vitro on LPS-stimulated macrophages. Macrophage inflammation was then induced using 10 μg/mL LPS. The anti-inflammatory effect of JMG was investigated by the quantitative polymerase chain reaction (qPCR) and ELISA. The anti-inflammatory mechanism was determined using western blotting, the electrophoretic mobility shift assay, and immunocytochemistry. Finally, the antimicrobial activity of JMG was verified by survival experiments in vivo and by bacterial culture experiments in vitro . Results: A 200 mg/kg water extract of JMG was safe for mice and had a significant protective effect on LPS-induced sepsis. Organ damage of heart, liver, lung and kidney was also significantly reduced at 24 h in the JMG group, when compared with the LPS group. The serum MIP-1α (CCL-3), MIP-1β (CCL-4), IL-1β, and TNFα cytokines were significantly decreased at 6 h in the JMG group, when compared with the LPS group. In a similar manner, 0.2μg/ml JMG significantly reduced mRNA and protein levels of MIP-1α (CCL-3), MIP-1β (CCL-4), IL-1β, and TNFα in LPS-stimulated macrophage. JMG treatment inhibited the phosphorylation of NF-κB p65 and reduced nuclear transduction, thus reducing transcriptional activity. At the same time, we showed that JMG had no protective effect on Escherichia coli -induced sepsis, as well as no antimicrobial activity. Conclusions: Our results showed that a water-soluble extract of JMG inhibited LPS-induced inflammation via attenuating the NF-κB signaling pathway, which provides an important rationale for the treatment of inflammation-related diseases. Graphical abstract: Image 1